Examining the relationship between foot medial arch height and short and medium distance running performances and some variables in athletes - Temur, H. B.; Esen, H.; Ince, O. B.; Karadag, H. (International Journal of Disabilities Sports and Health Sciences, 2024)
In this study, the relationship between foot medial arch height, age, height, body weight, body mass index (BMI), calf and thigh thickness and 100-meter and 3000-meter running performances in athletes was investigated. 28 athletes competing in national competitions, with an average age of 18.29±5.68 years, were included in the study on a voluntary basis. The right foot medial arch heights, heights, body weights, calf and thigh thicknesses of the participants were determined. BMI's were calculated. Also, 100 m and 3000 m. running times were determined. Data analyzes were performed using descriptive statistics and correlation tests. As a result of the analysis, 100 m running performance had a negative relationship with the values of height (r= -.377), body weight (r= -.466), BMI (r= -.428) and thigh circumference (r= -.433). It was observed that there was a relationship with the calf circumference measurement value (-.496) at the p<0.01 level. On the other hand, it was determined that the relationship between foot medial arch height (r= -.178) was not significant (p>0.05). On the other hand, 3000 m running performance was negatively affected by height (r= -.493), body weight (r= -.641), BMI (r= -.625) and calf girth thickness (r= -.623). It was determined that it showed significance at the p<0.01 level. It was also determined that there was a significant relationship with medial arch height in a negative direction (r = -.404) and at p < 0.05. As a result, it can be said that foot medial arch height, height, body weight, BMI, thigh and calf circumference thickness values are effective on short and medium distance running performances.